(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
There are some people that anindividual keeps in mind when making a purchase. Usually, such peopledisseminate opinions and other individuals are pressured into following theirtrend, becoming associated with them and using them as a standard of theirpurchase decisions. Such people are known as reference groups and they includeentertainment figures, sports heroes, political leaders, parents, co-workers,teachers and peers. This paper seeks to contribute to the existing body of theliterature on reference group influence. Specifically, it focuses on peerinfluence among young adults’ products purchase decisions. A convenience sample of 101 universitystudents participated in this study. The results of Analysis of Variance andt-tests indicated that there is more normative influence for a public luxury(sunglasses) than for a private luxury (cell phone) and private necessity(toothpaste). Informational influence was also more for a public luxury than aprivate necessity.